An exploration of reported mortality from cutaneous squamous cell carcinoma using death certification and cancer registry data. (30th August 2013) - Rose, R.F.; Boon, A.; Forman, D.; Merchant, W.; Bishop, R.; Newton‐Bishop, J.A.
Summary: Background: Cutaneous squamous cell carcinoma (cSCC) is increasing in incidence but mortality rates are low. Identifying high‐risk tumours is important when rationalizing clinical review for patients with cSCC. Objectives: To assess the accuracy of death certification in cases of reported fatal cSCC and to identify risk factors for fatal cSCC. Methods: A retrospective, observational study of cases of fatal cSCC over 11 years (1993–2004) in Leeds, identified in cancer registry and death certification data. Results: Fifty‐eight patients were recorded by the registry as having fatal cSCC in this period. Review of case notes and pathology specimens, where available (34 cases), confirmed that 21/34 patients had died of cSCC. Five were on the ear and none on the lip. Four patients had been treated for leukaemia or lymphoma and one was a renal transplant recipient. On pathology review five patients proved to have had malignant adnexal tumours rather than cSCC, and one a melanoma. In addition, three patients had disease of the ear canal or vulva. Conclusions: A proportion of deaths were falsely attributed to cSCC as a result of inaccurate histological diagnosis. Some fatalities were related to tumours in sites known to be at higher risk, and a significant proportion was postulated to be related to immunosuppression. In those cases attributed to cSCC in which this could be assessed, the majority were American Joint Committee on Cancer stage 2 and only 24% were in high‐risk sites. Abstract : What's already known about this topic? Mortality rates for cutaneous squamous cell carcinoma (cSCC) are low. Predictors of fatal cSCC include tumour site, size and depth, involvement of subcutaneous fat, perineural invasion and degree of differentiation. What does this study add? SCC of the genital skin should be coded consistently as vulval cancer by cancer registries, to reflect increased metastatic potential. Some poorly differentiated tumours reported as cSCC have been recategorized as malignant adnexal tumours on review with immunohistochemistry. Current clinical and pathology risk factors identify most but not all tumours with aggressive behaviour.